2006
DOI: 10.1016/j.theriogenology.2005.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the efficiency of embryo transfer in the domestic ferret (Mustela putorius furo)

Abstract: Embryo transfer (ET) to recipient females is a foundational strategy for a number of assisted reproductive technologies, including cloning by somatic cell nuclear transfer. In an attempt to develop efficient ET in domestic ferrets, factors affecting development of transferred embryo were investigated. Unilateral and bilateral transfer of zygotes or blastocysts in the oviduct or uterus was evaluated in recipient nulliparous or primiparous females. Developing fetuses were collected from recipient animals 21 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Zygotes were collected from the mating of sable coat color ferrets (Marshall BioResources) as previously described 31 . TALEN mRNA (50 ng/μl) was injected into the cytoplasm of zygotes using a micromanipulator and injector (Eppendorf) and a phase contrast microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zygotes were collected from the mating of sable coat color ferrets (Marshall BioResources) as previously described 31 . TALEN mRNA (50 ng/μl) was injected into the cytoplasm of zygotes using a micromanipulator and injector (Eppendorf) and a phase contrast microscope.…”
Section: Methodsmentioning
confidence: 99%
“…These studies demonstrated an 87% targeting efficiency (14 insertions/deletions in 16 alleles or 8 blastocysts that were amenable to analysis). Next, we injected 148 zygotes, incubated at 39°C for 24 h, and transferred 116 two-cell-stage embryos into the oviduct of pseudopregnant female sable ferrets as previously described 31 . Twenty-three ferrets were born and 11 survived.…”
Section: Methodsmentioning
confidence: 99%
“…2000; Lindeberg et al. 2002; Lindeberg 2003; Li et al. 2006a), and in all of these studies pseudopregnant females were used as recipients.…”
Section: Embryo and Semen Cryobanking And Associated Reproductive Tecmentioning
confidence: 99%
“…Ovulation was induced by mating recipients by either surgically (Lindeberg et al. 2002; Lindeberg 2003; Li et al. 2006a) or genetically (Amstislavsky et al.…”
Section: Embryo and Semen Cryobanking And Associated Reproductive Tecmentioning
confidence: 99%
“…Indeed, cloning of ferrets from cystic fibrosis transmembrane conductance regulator gene-targeted fibroblasts has recently generated a cystic fibrosis model in the ferret [3]. This species is also considered an excellent model for the recovery and conservation of related endangered species, such as the black-footed ferret and the European mink [4]. …”
Section: Introductionmentioning
confidence: 99%